THE LIMITS FOR THE GLOBAL PROLIFERATION OF COMPETITION LAW: THE CASE OF MACAO SAR - Alexandr Svetlicinii (European Scientific Journal, ESJ, 2014)
The adoption and enforcement of competition rules which replace or supplement state regulation of markets has become a global trend that led to almost universal proliferation of competition law regimes. Following the lead of the developed market economies an increasing number of developing countries and transition economies have introduced competition rules in their national legal systems. Macao SAR, as a small developed economy concentrated around booming gaming industry, stands among few jurisdictions that do not have comprehensive competition legislation. Present paper analyses current situation with regulation of market competition in Macao with special focus on the gaming industry. While general competition rules embedded in the Commercial Code are left to the private enforcement by interested parties, specific competition rules applied to the gaming activities have to be enforced by the sector regulator lacking the knowledge and experience in antitrust enforcement. As a result, the effective antitrust enforcement is largely non-existent. The international trade obligations of Macao SAR under the WTO framework or its bilateral trade relations with China and European Union have not prompted the adoption of competition law either. The study is an attempt to provide explanations as to the current state of affairs with competition rules and to anticipate further developments in this field.